2019
DOI: 10.1002/jia2.25246
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the HIV care continuum needed to meaningfully reduce HIV incidence among men who have sex with men in Baltimore, US: a modelling study for HPTN 078

Abstract: Introduction HIV prevalence is high among men who have sex with men (MSM) in Baltimore, Maryland, United States, and the levels of viral suppression among HIV‐positive MSM are relatively low. The HIV Prevention Trials Network 078 trial seeks to increase the levels of viral suppression among US MSM by increasing the rates of diagnosis and linkage to care and treatment. We estimated the increases in viral suppression needed to reach different HIV incidence reduction targets, and the impact of meeting diagnosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…4,5 The high HIV infection rate among US MSM has been associated with low condom use, 6 high numbers of non-steady partnerships, 7,8 and low levels of viral suppression because levels of both HIV diagnosis and retention in care among US MSM are suboptimal. [9][10][11] Baltimore, Maryland, is a major US city whose population is primarily non-Hispanic black or African American (63%) (hereafter referred to as black) and non-Hispanic white (hereafter referred to as white) (28%). 12 HIV prevalence among MSM in Baltimore, MD, estimated at 43% in 2011 and 37% in 2017, is one of the highest in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The high HIV infection rate among US MSM has been associated with low condom use, 6 high numbers of non-steady partnerships, 7,8 and low levels of viral suppression because levels of both HIV diagnosis and retention in care among US MSM are suboptimal. [9][10][11] Baltimore, Maryland, is a major US city whose population is primarily non-Hispanic black or African American (63%) (hereafter referred to as black) and non-Hispanic white (hereafter referred to as white) (28%). 12 HIV prevalence among MSM in Baltimore, MD, estimated at 43% in 2011 and 37% in 2017, is one of the highest in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…We used a previously published HIV transmission and treatment model for US MSM ( Mitchell et al, 2019 ), and included PrEP. Briefly, it is a deterministic compartmental model of sexual HIV transmission, which divides the population by age, race, HIV infection stage and HIV care continuum engagement.…”
Section: Methodsmentioning
confidence: 99%
“…The model was previously fitted to Baltimore MSM data in a Bayesian framework involving varying 117 parameters and giving 169 parameter combinations (model fits) which reproduce well HIV prevalence trends, demography and HIV care continuum outcomes ( Mitchell et al, 2019 ). We retained these 169 parameter combinations, and for each combination additionally selected PrEP parameter values giving PrEP coverage consistent with Baltimore MSM data ( Hoots et al, 2016 ; Centers for Disease Control and Prevention, 2019 ) (details in supplementary material ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Prior models evaluating the HIV care continuum for people with HIV in the United States (U.S.) have suggested that major improvements to HIV screening, care linkage, and care retention would be needed to achieve substantial reductions in HIV transmission. [10][11][12][13] Models focused on HIV-uninfected populations have projected the impact of PrEP given low coverage and poor persistence. [14][15][16] Despite this strong modeling research base, the potential for synergy between the HIV care and prevention continua has not been sufficiently evaluated.…”
Section: Introductionmentioning
confidence: 99%